Brand Design and Packaging Development to Upgrade the Eco Print Product of Women’s Group in Bang Khayang Subdistrict - Anukun, Monsicha (Journal of Graduate MCU KhonKaen Campus, 2026)
This research aims to 1) study the products, identity, and information of the women’s group in Bang Khayaeng Subdistrict, Mueang District, Pathum Thani Province. 2) study the needs of group members and target groups regarding the image of Eco Print products and 3) design brand identity and develop packaging for Eco Print products of the women’s group in Bang Khayaeng Subdistrict, Mueang District, Pathum Thani Province, by using a participatory community process. This research is a mixed-methods study, employing in-depth interviews, focus group discussions, and online questionnaires. The sample consists of 10 members of the women’s group in Bang Khayaeng Subdistrict and 30 target consumers. The research instruments used include semi-structured interviews and online questionnaires. Data collection was carried out through in-depth interviews, focus group discussions, participatory design activities, and questionnaires. Data analysis employed content analysis and descriptive statistical analysis. The research findings revealed that: 1) At the beginning, the women’s group in Bang Khayaeng Subdistrict produced tie-dyed fabrics using chemical dyes; later, they developed products with Eco Print dyeing techniques and found that the existing brand identity could not clearly communicate the product image. 2) Both group members and target consumers agreed that the product image should emphasize naturalness and simplicity; the original brand name should be retained but the brand identity should be modernized and clarified. 3) The selected brand identity was used as a prototype for designing packaging, hang tags, and stickers, using environmentally friendly materials.